4 sixths... 4/6, which can be simplified to 2/3. 1/2 + 1/6 = 2/3
3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6
8/-3 + -7/2 = 8x-2/-3x-2 + -7x3/2x3= -16/6 + -21/6= -37/6
3(x + 1)(x + 2)
2/3 is equal to 4/6, so 2/3 is greater than 1/6.
2/3 + 1/6 + 1/6 = 1
1/6 + 1/2 = 2/3
They add up to 7/6 or 1 and 1/6
2/3 + 1/6 + 1/6= 4/6 + 1/6 + 1/64 + 1 + 1 = 66/6 = 1
1
It is: 1/2+1/6 = 2/3
1/2 + 1/6 = 2/3
To calculate 2/3 + 1/6 + 1/6, we first need to find a common denominator for the fractions, which in this case is 6. Then, we convert each fraction to have a denominator of 6: 2/3 becomes 4/6, and 1/6 + 1/6 remains as 1/6 + 1/6. Adding these fractions together gives us 4/6 + 1/6 + 1/6 = 6/6, which simplifies to 1. Therefore, the calculation of 2/3 + 1/6 + 1/6 is equal to 1.
2 over 6 or 1 over 3
2/5 plus 1/3 plus 5/6 is equal to 1.57 or 1 57/100
1/3 = 2/6 + 1/6 = 3/6 or 1/2
-1/6 + -1/2 = -1/6 + -3/6 = -4/6